Classroom Furniture and Student Body Dimensions in East Malaysian Primary Schools - R.A R.. Ghazilla; Z. Taha; S.H.A. Rashid; Iskandar; Nazaruddin; S.H. Sajeli (ANIMA Indonesian Psychological Journal, 2006)
-